The Effectiveness of a Montessori-Based Structured Process in Teaching Self-Care Skills to Individuals with Autism: A Case Study on Nose Wiping Behavior - Сафіє Сунай Їлдирим Доґру; Селенай Гюлер (Preschool Education: Global Trends, 2025)
Introduction. The importance of this research it contributes to the literature by demonstrating that self-care behavior such as nose wiping can be effectively taught to children with special needs through structured instructional processes. This Montessori-supported practice offers a unique teaching approach that enhances both physical coordination and hygiene habits.